"Behave like a responsible adult" – Relation between social identity and psychosocial skills at stake in self-management of a chronic disease. Issue 2 (4th March 2018) - Fonte, David; Lagouanelle-Simeoni, Marie-Claude; Apostolidis, Thémis
Abstract: We show that the development of psychosocial skills promoting self-management of a chronic disease is associated with the acquisition of a social identity valued in the ideological context of reference. To do this, we focus on a skill that is important for people suffering from a chronic disease to acquire: Assuming responsibility for self-managing one's own pathology. Because acting responsibly is also a skill socially attributed to the identity of adults in Western liberal societies, we studied the chronically ill's sense of belonging to the adult social group. In Study 1 ( N  = 102 diabetics), we suggested that behaving like a "responsible adult" in the self-management of a chronic disease is socially valued. In Study 2 ( N  = 261 diabetics), we suggested that identification with this group is associated with a feeling of responsibility promoting improved self-management behaviors. The results obtained from the two studies are consistent with our hypotheses. They allow us to conceptualize psychosocial skills through the identity, ideological and normative issues that underpin their development.